Association of the vitamin D binding protein polymorphisms with the risk of type 2 diabetes mellitus: a meta-analysis. Issue 11 (4th November 2014) - Wang, Gaoshuai; Li, Yuqian; Li, Linlin; Yu, Fei; Cui, Lingling; Ba, Yue; Li, Wenjie; Wang, Chongjian
Abstract : Objective: Previous studies on the association between vitamin D binding protein ( DBP ) polymorphisms and the risk of type 2 diabetes mellitus (T2DM) have produced conflicting results. The purpose of this meta-analysis was to examine whether DBP polymorphisms are associated with the risk of T2DM. Design: Systematic review and meta-analysis. Methods: All eligible studies were searched and acquired from the Cochrane, Pubmed, ISI, CNKI (Chinese) and Wanfang (Chinese) databases. ORs with corresponding 95% CIs were computed to estimate the association between DBP polymorphisms and T2DM. In addition, heterogeneity test, meta-regression and sensitivity analysis were also conducted. Results: Six studies, which included 1191 cases and 882 controls, met the inclusion criteria and were included in the meta-analysis. The results showed that no significant associations were found between codon 416 and codon 420 polymorphisms in the DBP and the risk of T2DM in the overall analyses. In stratified analysis, significant associations between the codon 420 polymorphism and T2DM were found in Asians (allele Lys vs Thr: OR (95% CI) 1.49 (1.19 to 1.85), genotype Lys/Thr versus Thr/Thr: OR (95% CI) 1.80 (1.36 to 2.38), and Lys/Thr+Lys/Lys versus Thr/Thr: OR (95% CI) 1.81 (1.37 to 2.39), respectively) but not in Caucasians. For the codon 416, the significant association with T2DM was also detected in Asians (genotype Glu/Asp+Glu/Glu vs Asp/Asp: OR (95% CI) 1.36 (1.04 to 1.78)) but not in Caucasians. Conclusions: This meta-analysis demonstrated that the DBP polymorphism was moderately associated with increased susceptibility to T2DM in Asians, but a similar association was not found in Caucasians. It suggested that ethnicity might be the potential factor associated with heterogeneity.